ANALISIS IMPLEMENTASI PENGUATAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN PPKn (STUDI KASUS DI SD NEGERI 1 SUROTRUNAN TAHUN AJARAN 2019/2020) - Wibowo, Nadya Vera; Rokhmaniyah, Rokhmaniyah; Suryandari, Kartika Christy (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
It is crucial to implement student character values from early age. The application of character education has been implemented at S D N 1 Surotrunan. To determine the of student character values, the researcher was interested in evaluating the implementation of strengthening character education at S D N 1 Surotrunan. The study aimed to describe the implementation of strengthening character education in Pancasila and Civic Education and to analyze the factors that affected strengthening character education in Pancasila and Civic Education at S D N 1 Surotrunan. The data were narration about research subjects obtained through data collection techniques included observation, interviews, and document study. The participants were students, class teachers, and principal. The data validity test techniques were source triangulation and technique triangulation. Data analysis techniques were data reduction, data presentation, and verification. (1) The student character values that can be observed in SD Negeri 1 Surotrunan are: (a) religious; (b) honest; (c) tolerance; (d) discipline; (e) care for the environment; (f) social care; (g) and responsibilities. Overall, the students' character values have been optimal, there are only a few values that have not been fulfilled optimally. Values that are not optimal in instilling character values are tolerance, environmental care, and social care; (2) factors affecting the strengthening character education in Pancasila and Civic Education were internal and external factors. Internal factors included: (a) feeling, (b) habit, (c) willingness, (d) mood, and (e) offspring. External factors included education and environment.